Decision making in beach volleyball defense: Crucial factors derived from interviews with top-level experts - Schläppi-Lienhard, O.; Hossner, E. J. (Psychology of Sport and Exercise, 2015)
Objectives: In fast ball sports like beach volleyball, decision-making skills are a determining factor for excellent performance. The current investigation aimed to identify factors that influence the decision-making process in top-level beach volleyball defense in order to find relevant aspects for further research. For this reason, focused interviews with top players in international beach volleyball were conducted and analyzed with respect to decision-making characteristics. Design: Nineteen world-tour beach volleyball defense players, including seven Olympic or world champions, were interviewed, focusing on decision-making factors, gaze behavior, and interactions between the two. Methods: Verbal data were analyzed by inductive content analysis according to Mayring (2008). This approach allows categories to emerge from the interview material itself instead of forcing data into pre-set classifications and theoretical concepts. Results: The data analysis showed that, for top-level beach volleyball defense, decision making depends on opponent specifics, external context, situational context, opponent's movements, and intuition. Information on gaze patterns and visual cues revealed general tendencies indicating optimal gaze strategies that support excellent decision making. Furthermore, the analysis highlighted interactions between gaze behavior, visual information, and domain-specific knowledge. Conclusions: The present findings provide information on visual perception, domain-specific knowledge, and interactions between the two that are relevant for decision making in top-level beach volleyball defense. The results can be used to inform sports practice and to further untangle relevant mechanisms underlying decision making in complex game situations.